Advances in organic photovoltaic cells: a comprehensive review of materials, technologies, and performance - Solak, Ebru Kondolot; Irmak, Erdal (RSC advances, 2023)
This paper provides a comprehensive overview of organic photovoltaic (OPV) cells, including their materials, technologies, and performance. In this context, the historical evolution of PV cell technology is explored, and the classification of PV production technologies is presented, along with a comparative analysis of first, second, and third-generation solar cells. A classification and comparison of PV cells based on materials used is also provided. The working principles and device structures of OPV cells are examined, and a brief comparison between device structures is made, highlighting their advantages, disadvantages, and key features. The various parts of OPV cells are discussed, and their performance, efficiency, and electrical characteristics are reviewed. A detailed SWOT analysis is conducted, identifying promising strengths and opportunities, as well as challenges and threats to the technology. The paper indicates that OPV cells have the potential to revolutionize the solar energy industry due to their low production costs, and ability to produce thin, flexible solar cells. However, challenges such as lower efficiency, durability, and technological limitations still exist. Despite these challenges, the tunability and versatility of organic materials offer promise for future success. The paper concludes by suggesting that future research should focus on addressing the identified challenges and developing new materials and technologies that can further improve the performance and efficiency of OPV cells. The paper analyzes the key features, performance, efficiency, and electrical characteristics of organic PV cells to highlight the latest trends and advancements by using comparative tables and a comprehensive SWOT analysis.